Antioxidant and anticholinesterase effects of frequently consumed cereal grains using in vitro test models - Senol, F. Sezer; Kan, Asuman; Coksari, Gulay; Orhan, Ilkay Erdogan (Informa Healthcare, 2012)
The ethyl acetate and ethanol extracts obtained from eight varieties (Faikbey, Y-1779, CI-8357, Cheokota, Seydisehir, Y-330, Sivas and YVD-18) of oat (Avena sativa L.), one variety (Larende) of barley (Hordeum vulgare L.), one variety (Tatlicak 97) of triticale (Triticale sp.) and one rye variety (Aslim 95) (Secale cereale L.) were investigated for their antioxidant effects in seven test systems. Anticholinesterase activity of the extracts was examined by enzyme-linked immunosorbent assay (ELISA) microplate reader. Total phenol and flavonoid contents were calculated using Folin Ciocalteau and AlCl3 reagents, respectively. All of the extracts were ineffective in cholinesterase inhibition assays and had weak-to-moderate activity in antioxidant assays. The extracts exerted better activity in iron-chelation capacity ranging between 43.17 +/- 2.04 and 62.97 +/- 1.29%. Triticale extracts showed higher activity in reducing power experiments. A notable difference in the results of the antioxidant activity assays was observed among the oat varieties.
Keywords: cereal grains; Poaceae; antioxidant activity; anticholinesterase activity